2019
DOI: 10.1186/s12885-018-5168-x
|View full text |Cite
|
Sign up to set email alerts
|

Total hysterectomy versus uterine evacuation for preventing post-molar gestational trophoblastic neoplasia in patients who are at least 40 years old: a systematic review and meta-analysis

Abstract: BackgroundThe clinical value of total hysterectomy for patients with hydatidiform mole (HM) being at least 40 years old remains highly controversial. Since the practice of hysterectomy has been applied globally for decades, there is an urgent need to perform a systematic review to assess its risks and benefits.MethodsSix electronic databases, including four English databases and one Chinese database, were searched from the inception of each database till October 6th 2017. Studies were included if they: 1) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 21 publications
0
22
0
4
Order By: Relevance
“…Hysterectomy is an alternative to suction D&E for molar evacuation in selected patients who do not wish to preserve childbearing ( Box 2 ), especially in women older than the age of 40 years, because these patients have a higher risk of postmolar gestational trophoblastic neoplasia. 3 , 13 , 16 Usually the adnexa may be preserved, even if theca lutein cysts are present. Hysterectomy reduces the risk of malignant postmolar sequelae to approximately 3–5% compared with approximately 15–20% after evacuation by D&E. 3 , 13 , 16 Because hysterectomy does not eliminate the possibility of postmolar gestational trophoblastic neoplasia these patients should also be monitored postoperatively with serial hCG levels.…”
Section: Hydatidiform Molementioning
confidence: 99%
See 1 more Smart Citation
“…Hysterectomy is an alternative to suction D&E for molar evacuation in selected patients who do not wish to preserve childbearing ( Box 2 ), especially in women older than the age of 40 years, because these patients have a higher risk of postmolar gestational trophoblastic neoplasia. 3 , 13 , 16 Usually the adnexa may be preserved, even if theca lutein cysts are present. Hysterectomy reduces the risk of malignant postmolar sequelae to approximately 3–5% compared with approximately 15–20% after evacuation by D&E. 3 , 13 , 16 Because hysterectomy does not eliminate the possibility of postmolar gestational trophoblastic neoplasia these patients should also be monitored postoperatively with serial hCG levels.…”
Section: Hydatidiform Molementioning
confidence: 99%
“… 3 , 13 , 16 Usually the adnexa may be preserved, even if theca lutein cysts are present. Hysterectomy reduces the risk of malignant postmolar sequelae to approximately 3–5% compared with approximately 15–20% after evacuation by D&E. 3 , 13 , 16 Because hysterectomy does not eliminate the possibility of postmolar gestational trophoblastic neoplasia these patients should also be monitored postoperatively with serial hCG levels. 3 , 13 , 16 …”
Section: Hydatidiform Molementioning
confidence: 99%
“…For those who have completed childbearing and have a presumed molar pregnancy, hysterectomy provides an alternative method of management. In one study, compared to uterine evacuation, hysterectomy has a significant advantage in preventing post-molar GTN with an approximately 80% reduction in risk [29]. Although hysterectomy eliminates any locally invasive disease, some women will have occult metastases at the time of diagnosis and therefore hCG monitoring is still warranted after hysterectomy [29].…”
Section: Molar Pregnancymentioning
confidence: 99%
“…Suction curettage is the preferred treatment for complete hydatidiform mole, especially for patients with fertility requirements [ 15 ]. However, total hysterectomy may be appropriate for perimenopausal patients who have already given birth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the removal of the hydatidiform tissue, total hysterectomy can reduce the need for subsequent chemotherapy by eliminating the risk of local muscular layer infiltration [ 16 ]. Zhao et al [ 15 ] showed that the incidence of progression to GTN after suction curettage in high-risk hydatidiform mole patients above 40 years old was 44%. Total hysterectomy could reduce the possibility of GTN progression, but 13% of patients could still progress to GTN [ 16 ].…”
Section: Discussionmentioning
confidence: 99%